2017
DOI: 10.1038/s41598-017-12482-5
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone based optical spectrometer for diffusive reflectance spectroscopic measurement of hemoglobin

Abstract: We report a miniature, visible to near infrared G-Fresnel spectrometer that contains a complete spectrograph system, including the detection hardware and connects with a smartphone through a microUSB port for operational control. The smartphone spectrometer is able to achieve a resolution of ~5 nm in a wavelength range from 400 nm to 1000 nm. We further developed a diffuse reflectance spectroscopy system using the smartphone spectrometer and demonstrated the capability of hemoglobin measurement. Proof of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…(c) A smartphone spectrometer configuration with optical fiber and micro USB interface for operation. Reprinted from . CC BY 4.0.…”
Section: Smartphone‐based Imaging Technologiesmentioning
confidence: 99%
“…(c) A smartphone spectrometer configuration with optical fiber and micro USB interface for operation. Reprinted from . CC BY 4.0.…”
Section: Smartphone‐based Imaging Technologiesmentioning
confidence: 99%
“…Fortunately, several portable spectrometers have become commercially available due to advancements in sensor and IT technology; e.g., startup companies such as Stratio, SCiO, and TellSpec have developed pocket-sized spectrometers [1][2][3]. Several research groups recently demonstrated that a low-cost smartphone spectrometer can be designed using off-the-shelf components [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated recently that incorporation of advanced optical systems into smartphone platforms is a useful development [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In our previous work, we developed a digital camera-based portable imaging spectrometer to detect reflectance spectra from the ocean, a lake, and a human hand [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%